Polysaccharide Hydrogels Based on Cellulose and Chitosan for Drug Sustained-Release Applications - Xueyan Jin; Hong Xu; Zhiping Mao; Xueling Feng; Yi Zhong (Applied Sciences)
This study developed a novel water-soluble Cellulose Acetoacetate (CAA)-chitosan (CS) composite hydrogel drug delivery system. In this system, CAA and CS molecules are cross-linked via dynamic enamine bonds, forming a three-dimensional network structure suitable for drug encapsulation and controlled release. The primary objective was to address the challenges associated with the short half-life and significant fluctuations in therapeutic concentration of cytokine drugs, such as interleukin-2 (IL-2). A hydrogel system with a three-dimensional spatial network structure was successfully constructed via dynamic enamine bonds cross-linking between the acetoacetate groups in CAA molecules and the amino groups in CS. This system exhibits the following characteristics: (1) Dynamic covalent bonds impart adjustable mechanical properties to the hydrogel, enabling precise control over gelation time and mechanical performance; (2) A hierarchical pore structure (average pore size of 100–200 μm) provides a three-dimensional confined space for efficient drug encapsulation, achieving an IL-2 encapsulation efficiency of 83.3 ± 3.1%; (3) In vitro release studies demonstrated that the cumulative release of IL-2 within 72 h ranged from 18.4% to 34.7%, indicating sustained-release behavior. Cell viability assays confirmed that the hydrogel maintained the survival rate of L929 cells above 85% (as determined by the CCK-8 method), and live/dead staining revealed no apparent cytotoxicity. Overall, this three-dimensional network hydrogel based on dynamic covalent bonds represents a promising strategy for low-dose, long-lasting cytokine delivery.